Exploring the role of the lateral gluteal muscles in running: Implications for training - Fetters, K. A. (Strength and Conditioning Journal, 2020)
Gluteal-strengthening exercises are widely used for improving running performance. However, as running occurs primarily in the sagittal plane, such strength exercises have focused on the gluteus maximus and its role in producing ground reaction forces as a hip extensor. Meanwhile, strength deficits in the lateral gluteal muscles, the medius and minimus, are common among runners. This article will explore the role of the lateral gluteal muscles in running kinematics, performance, and injury, with implications for strength and conditioning professionals, sports medicine specialists, and physical therapists. Recommendations for strengthening the gluteus medius and minimus in runners will follow.